A magnetorheological fluid based planetary gear transmission for mechanical power-flow control. (4th March 2021) - Christie, M D; Sun, S; Quenzer-Hohmuth, J; Deng, L; Du, H; Li, W H
Abstract: Power transmission for mechanical systems often involves the use of clutching- or dissipative-elements to protect drive systems and provide steady output power. As standard implementations in motor-driven systems, these devices operate passively or in discrete states, providing limited controllability to the power output. This paper presents a magnetorheological-fluid-based differential (planetary) gear transmission which serves to variably couple motor power through a sun gear input to a load affixed to a planet carrier output. This is achieved both rapidly and continuously through controlled slippage between the ring gear of the device and its casing. Compared to conventional MR clutches, the unique functionality of the differential gearbox enables use of an MR brake with lower inertia than an in-line clutch. Through control of current supplied to the energizing electromagnet of brake component of the transmission, simple and reversible governing of output torque and speed is achieved. This behaviour is modelled and verified through testing, showing a 349% variation in brake torque for constant speed tests from the off state to the maximum capacity of the device, with a 262% variation in brake torque under a harmonic input displacement also observed. The versatility of the device demonstrated through PID speed and torque control.